Foreword: The Rehnquist Court and the First Amendment - Neil M. Richards (Washington University Journal of Law & Policy, 2006)
This paper introduces the question – what will be the legacy of the Rehnquist Court? Although it is too early to say with certainty, it is safe to hazard a guess that it will be remembered as a relatively conservative Court, particularly interested in policing the lines between federal and state power in areas such as the federal commerce power, state sovereign immunity, and criminal procedure. Indeed, it is in these areas that the “Rehnquist Court” is most aptly named, for William Rehnquist was a leader of the Court’s doctrinal evolution in these areas in a number of ways. Despite the Court’s emphasis on federalism and constitutional criminal law, issues of First Amendment law remained consistently at the top of the docket in terms of importance. Over its two decades, the Rehnquist Court grappled with a host of fundamental First Amendment issues, involving a panoply of questions basic to any free society. Among many others, it addressed questions of flag burning, hate speech, sexually-explicit speech, speech in the digital environment, free speech versus the right to privacy, free speech and the regulation of intellectual property, the scope of the rights of expressive association and religious free exercise,9 and the prohibition on the establishment of religion.
Keywords: First Amendment protections (United States Constitution); William H. Rehnquist; 1924-2005; United States. Supreme Court; The Rehnquist Court; First Amendment law; Free speech; Internet; Jurisprudence